2013
DOI: 10.1002/chem.201303347
|View full text |Cite
|
Sign up to set email alerts
|

Epimerization‐Free C‐Terminal Peptide Activation

Abstract: Smooth operation: C‐terminal peptide activation with full stereointegrity was accomplished using a copper(II)‐mediated coupling reaction of carboxylic acids with arylboroxines (see scheme, NCL = native chemical ligation, Boc = tert‐butoxycarbonyl). This method allows epimerization‐free activation and ligation of peptides with racemization‐prone phenylglycine at the C terminus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…In earlier work we and others have shown that carboxylic acids can be conveniently transformed into aryl esters using the CLE reaction from aryl boronic acids or boroxines . Starting from arylboroxines, the CLE reaction even allows C‐terminal activation of peptides as aryl esters that were used in subsequent amidation reactions without loss of stereointegrity . In this letter we report the efficient synthesis of a wide variety of enol esters from commercially available alkenylboronic acids and boroxine pyridine complexes and some useful follow up transformations such as aminolysis, trans(thio)esterification, reduction, aminal and cyanohydrin ester formation.…”
Section: Methodsmentioning
confidence: 99%
“…In earlier work we and others have shown that carboxylic acids can be conveniently transformed into aryl esters using the CLE reaction from aryl boronic acids or boroxines . Starting from arylboroxines, the CLE reaction even allows C‐terminal activation of peptides as aryl esters that were used in subsequent amidation reactions without loss of stereointegrity . In this letter we report the efficient synthesis of a wide variety of enol esters from commercially available alkenylboronic acids and boroxine pyridine complexes and some useful follow up transformations such as aminolysis, trans(thio)esterification, reduction, aminal and cyanohydrin ester formation.…”
Section: Methodsmentioning
confidence: 99%
“…33 For example, Crich and Banerjee applied this strategy with a β-thiolfunctionalized phenylalanine for the synthesis of decapeptides.33a Recently, our group reported an epimerization-free synthesis of activated aryl ester of small peptides (e.g. 4-(methylsulfonyl)phenyl esters) via the Chan-Lam coupling 34. These esters were successfully applied in native chemical ligation thus avoiding the addition of thiophenol to the reaction mixture for the in situ generation of a thiol ester as in the more common procedure.…”
mentioning
confidence: 99%
“…We thus conclude that the compound PC-d/l-Pgl-Me is a mixture of d-and l-enantiomer in ratio of 2.1:1 in favour for d-enantiomer. The epimerization of Pgl is known to occur very easily using standard coupling conditions and thus stereoselective synthesis would require specific reagents not employed in this work[44]. Chiral HPLC analysis was performed for enantiomeric mixture PC-d/l-Pgl-Me, racemic mixtures (PC-dl-Ala-Me, PC-dl-Leu-Et, PC-dl-Phe-Et, PC-dl-Val-Et) and for the samples of which we had the complete couple of antipodes.…”
mentioning
confidence: 99%